Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1128/jb.127.3.1543-1549.1976
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the rodlet layer of Trichophyton mentagrophytes microconidial wall

Abstract: The rodlet layer of the microconidial wall of Trichophyton mentagrophytes was isolated and partially characterized. The purified microconidial walls were first extracted with urea (8 M), mercaptoethanol (1%), and sodium dodecyl sulfate (1%) followed by enzymatic digestion with glusulase (snail intestinal enzymes) and purified (1-*3)-,8-D-glucanase and chitinase. The purified rodlet layer was 15 to 30 nm thick and accounted for approximately 10% ofthe original wall weight. The pattern of rodlet patches, as reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…lb). These individual fibres seem to be similar to the rodlets reported previously in the walls of the yeast phase of Paracoccidiodes brasiliensis [10], hyphal walls of Schizophyllum commune [9], microconidial walls of Trichophyton mentagrophytes [11] and spore walls of A. bisporus…”
Section: Resultssupporting
confidence: 83%
“…lb). These individual fibres seem to be similar to the rodlets reported previously in the walls of the yeast phase of Paracoccidiodes brasiliensis [10], hyphal walls of Schizophyllum commune [9], microconidial walls of Trichophyton mentagrophytes [11] and spore walls of A. bisporus…”
Section: Resultssupporting
confidence: 83%
“…Rodlet layers had, however, been described on fungal structures before any systematic study of hydrophobins. Characterization of these layers had shown many properties similar to those later described for some hydrophobins, such as being highly resistant to attempts to dissolve them by chemicals [54]. The connection between hydrophobins and rodlets was made by studying hydrophobin deletion mutants [26][27][28].…”
Section: Rodletsmentioning
confidence: 70%
“…Structurally similar surface layers have been observed on the cell walls of hyphomycetes and the hymenial layer in basidiomycetes (summarized by Honegger, 1984), in cotton fibres (Ryser, Meier & Holloway, 1983;Yatsu, Espelie & Kolattukudy, 1983;Ryser & Holloway, 1985) and at the poUen-stigma interface in angiosperms. In conidia this surface layer is composed of proteins (Hashimoto, Wu-Yuan & Blumenthal, 1976;Beever, Redgwell & Dempsey, 1979) or proteins and lipids (Cole & Pope, 1981). Beever & Dempsey (1978) demonstrated that the surface layer of conidial cell walls renders these spores water-repellent.…”
Section: Resultsmentioning
confidence: 99%